Faktor Faktor Yang Mempengaruhi Kualitas Pelayanan Publik Pada Kantor Kecamatan Marobo Kabupaten Muna - Andriani, Lisa; Basri, Muhammad; Mustakim, Mustakim (Universitas Halu Oleo, 2020)
This study aims to see the quality of public services organized by the Marobo District Government of Muna Regency and the factors that affect the quality of public services. This type of research uses qualitative methods. The data research technique was carried out through literature and field studies in the form of observations, interviews, agency data and documentation. The results showed that the quality of public services at the Marobo sub-district office in Muna Regency was good. This gives people satisfaction who feel comfortable when receiving services such as services that do not take time, tariffs for services are appropriate, and document security in the office is good. Meanwhile, the factors that affect the quality of public services at the Marobo sub-district office, Muna Regency, are inadequate work facilities that support the quality of service so that it has an impact on the quality of public services. This is a response to the shortage of seats, the absence of air conditioning and television at the Marobo sub-district office in Muna Regency.